The importance of suspecting superficial siderosis of the central nervous system in clinical practice. Issue 2 (23rd January 2004) - Messori, A; Di Bella, P; Herber, N; Logullo, F; Ruggiero, M; Salvolini, U
Abstract : Once the central nervous system surface is greatly encrusted with haemosiderin, even removing the source of bleeding will have little effect on the progression of clinical deterioration. Superficial siderosis of the central nervous system is rare and insidious, but magnetic resonance imaging has turned a previously late, mainly autoptical diagnosis into an easy, specific, in vivo, and possibly early one. Avoiding long diagnostic delay will be very important in those cases susceptible of causal treatment.